2018
DOI: 10.1371/journal.ppat.1007240
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated hemolysin liberates bacterial outer membrane vesicles for cytosolic lipopolysaccharide sensing

Abstract: Inflammatory caspase-11/4/5 recognize cytosolic LPS from invading Gram-negative bacteria and induce pyroptosis and cytokine release, forming rapid innate antibacterial defenses. Since extracellular or vacuole-constrained bacteria are thought to rarely access the cytoplasm, how their LPS are exposed to the cytosolic sensors is a critical event for pathogen recognition. Hemolysin is a pore-forming bacterial toxin, which was generally accepted to rupture cell membrane, leading to cell lysis. Whether and how hemol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…genes encoding for hemolysin which were also associated with low RFI (K06442) and low FCR (K11068). Although hemolysin is generally produced by pathogenic bacteria for nutrient acquisition by initiating host cell lysis, it has been suggested that hemolysin can promote activation of inflammasome signals reducing pathogen colonization in the intestine (Chen et al, 2018). Results related to Eubacterium might be a good example of possible gastrointestinal cross-talk from bacteria detected in the rumen having a possible effect on the lower gut.…”
Section: Possible Microbial Mechanisms Detected In High Feed Efficienmentioning
confidence: 99%
“…genes encoding for hemolysin which were also associated with low RFI (K06442) and low FCR (K11068). Although hemolysin is generally produced by pathogenic bacteria for nutrient acquisition by initiating host cell lysis, it has been suggested that hemolysin can promote activation of inflammasome signals reducing pathogen colonization in the intestine (Chen et al, 2018). Results related to Eubacterium might be a good example of possible gastrointestinal cross-talk from bacteria detected in the rumen having a possible effect on the lower gut.…”
Section: Possible Microbial Mechanisms Detected In High Feed Efficienmentioning
confidence: 99%
“…Another study revealed that CFT073 lacking D-serine deaminase had enhanced expression of hlyA and fimbriae genes, thereby contributing to increased bacterial colonization (60). Finally, a recent study demonstrated that, in E. tarda, OMV-associated HlyA enabled delivery of LPS to the cytoplasm and noncanonical inflammasome activation, as well as bacterial clearance in an oral challenge model (58). These studies support our findings that HlyA is an important regulator of bladder colonization and are consistent with the view that UPEC employs active mechanisms to limit HlyA expression to prevent host-protective inflammasome responses.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the levels of HlyA produced by a particular UPEC strain influence the distribution of this toxin to outer membrane vesicles (OMVs), which in some studies using E. coli have been shown to contain HlyA (56,57). Moreover, OMV-associated HlyA has been shown to initiate host cell death responses in the case of enterohemorrhagic E. coli (57), as well as the enteric pathogen Edwardsiella tarda (58). Because OMVs can influence numerous other immune cell functions (59), differential effects of HlyA expression levels on host protection vs. colonization may relate to variation in HlyA distribution to OMVs.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial OMVs can also trigger host innate sensing machinery (e.g., inflammasome pathways), which helps to increase bacterial clearance (17). In particular, bacteria-released OMVs promote caspase-11mediated non-canonical inflammasome responses via OMVbound LPS (18,24,25). OMV-mediated intracellular delivery of LPS results in the activation of caspase-11, a cytosolic LPS sensor, with the help of GBPs (19).…”
Section: Discussionmentioning
confidence: 99%